Adsorption and Oxidation of Aromatic Amines on Metal(II) Hexacyanocobaltate(III) Complexes: Implication for Oligomerization of Exotic Aromatic Compounds - Rachana Sharma; Md. Asif Iqubal; Sohan Jheeta; Kamaluddin (Inorganics, 2017)
Based on the hypothesis on the presence of double metal cyanides in the primordial oceans, a series of nano-sized metal(II) hexacyanocobaltate(III) (MHCCo) with the general formula: M3[Co(CN)6]2•xH2O (where M = Zn, Fe, Ni and Mn) has been synthesized. Surface interaction of aromatic amines, namely aniline, 4-chloroaniline, 4-methylaniline and 4-methoxyaniline with MHCCo particles has been carried out at the concentration range of 100–400 μM at pH~7.0. The percentage binding of aromatic amines on MHCCo surface was found to be in the range of 84%–44%. The trend in adsorption was in accordance to the relative basicity of the studied amines. At the experimental pH, amines reacted rapidly with the surface of the iron(II) hexacyanocobaltate, producing colored products that were analyzed by Gas Chromatography Mass Spectroscopy (GC-MS). GC-MS analysis of the colored products demonstrated the formation of dimers of the studied aromatic amines. Surface interaction of aromatic amines with MHCCo was studied by Fourier Transform Infrared (FT-IR) spectroscopy and Field Emission Scanning Electron Microscopy (FE-SEM). The change in amine characteristic frequencies, as observed by FT-IR, suggests that interaction took place through the NH2 group on amines with metal ions of hexacyanocobaltate complexes. FE-SEM studies revealed the adherence of 4-methoxyaniline on zinc hexacyanocobaltate particles surface. We proposed that MHCCo might have been formed under the conditions on primitive Earth and may be regarded as an important candidate for concentrating organic molecules through the adsorption process.